IOC consensus statement: ''training the elite child athlete'' - Mountjoy, M.; Armstrong, N.; Bizzini, L.; Blimkie, C.; Evans, J.; Gerrard, D.; Hangen, J.; Knoll, Ka.; Micheli, L.; Sangenis, P.; Van Mechelen, W. (British Journal of Sports Medicine, 2008)
Protecting the health of the athlete is the primary goal of the International Olympic Committee`s Medical Commission. One of its main objectives is the promotion of safe practices in the training of the elite child athlete. The elite child athlete is one who has superior athletic talent, undergoes specialised training, receives expert coaching and is exposed to early competition. Sport provides a positive environment that may enhance the physical growth and psychological development of children. This unique athlete population has distinct social, emotional and physical needs which vary depending on the athlete`s particular stage of maturation. The elite child athlete requires appropriate training, coaching and competition that ensure a safe and healthy athletic career and promote future well-being. This document reviews the scientific basis of sports training in the child, the special challenges and unique features of training elite children and provides recommendations to parents, coaches, health care providers, sport governing bodies and significant other parties.